2015
DOI: 10.1002/icd.1923
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind and Children's Trait Attributions about Average and Typically Stigmatized Peers

Abstract: Previous research indicates that children hold negative beliefs about peers with foreign accents, physical disabilities, and people who are obese. The current study examined skills associated with individual differences in children's social judgements about these typically stereotyped groups. Theory of mind, memory, and cognitive inhibition were assessed in 3-to 6-year-olds. Then, children were asked to make trait attributions and behavioural predictions about story characters' willingness to help a peer. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 103 publications
0
11
0
2
Order By: Relevance
“…Stereotypes and prejudices toward particular social groups may bias these interactions. In studies with adults, there is evidence that some cognitive skills may help promoting healthy social relationships based on an egalitarian and non-discriminatory behavior (e.g., Bartholow et al, 2006; Lapan and Boseovski, 2015). In this context, abilities necessary to implement goal-directed behavior and understanding others’ thoughts and feelings may strengthen positive interracial interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereotypes and prejudices toward particular social groups may bias these interactions. In studies with adults, there is evidence that some cognitive skills may help promoting healthy social relationships based on an egalitarian and non-discriminatory behavior (e.g., Bartholow et al, 2006; Lapan and Boseovski, 2015). In this context, abilities necessary to implement goal-directed behavior and understanding others’ thoughts and feelings may strengthen positive interracial interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Another ToM-related skill, the so-called self-presentation ToM, is understood as the concern about and regulation of the impression caused on other people, and has been linked to the tendency to make positive trait attributions to outgroup members (Aboud, 2013; Nesdale, 2013; Rutland, 2013). The research by Lapan and Boseovski (2015) is, to our knowledge, the only study that analyzed the role of skills related to both EF and ToM in trait attributions and behavioral predictions held by children 3 to 6 years of age toward typical peers and peers belonging to certain stigmatized social groups (obese children, children with disabilities, and children with foreign accents). They found that only ToM played a role in assessments of characters from stigmatized groups.…”
Section: Introductionmentioning
confidence: 99%
“…Frente a la impulsividad también se obtuvieron hallazgos, encontrando relación entre la ToM y las conductas agresivas (Centifanti et al, 2015;Sharp & Vanwoerden, 2014;Stellwagen & Kerig, 2013;Velotti et al, 2016). En lo referente a la exclusión social, pudo hallarse una relación entre ambas variables donde se menciona que menores puntuaciones de ToM muestran mayores fenómenos de exclusión social inclusive desde etapas tempranas del desarrollo (Lapan & Boseovski, 2015).…”
Section: Discussionunclassified
“…For example, children with stronger social imaginations: have more positive social skills (Watson, Nixon, Wilson, & Capage, 1999); are more prosocial, have larger social networks, healthier friendships, and are viewed more positively by peers (Caputi, Lecce, Pagnin, & Banerjee, 2012). Children who are more prosocial, in turn, have higher achievement (Miles & Stipek, 2006; Wentzel, 1993); have fewer angry responses in personal interactions and misbehave less at home and school (Mohr, Howells, Gerace, Day, & Wharton, 2007; Sharp, 2008); have stronger moral development, are less likely to stereotype, and more likely to attribute positive traits and expected behaviors to typically stereotyped characters (Baird & Astington, 2004; Galinsky & Moskowitz, 2000; Lapan & Boseovski, 2016; Levy & Dweck, 1998; Mulvey, Rizzo, & Killen, 2016); have better self-regulation (Carlson et al, 2015); and are more able to understand complex narratives, idiomatic expressions, and irony (Caillies & Le Sourn-Bissaoui, 2008; Filippova & Astington, 2008). …”
Section: Different Dimensions Of Developmentmentioning
confidence: 99%
“…have stronger moral development, are less likely to stereotype, and more likely to attribute positive traits and expected behaviors to typically stereotyped characters (Baird & Astington, 2004; Galinsky & Moskowitz, 2000; Lapan & Boseovski, 2016; Levy & Dweck, 1998; Mulvey, Rizzo, & Killen, 2016);…”
Section: Different Dimensions Of Developmentmentioning
confidence: 99%